ESL Teachers’ and Students’ Experience of Online Learning via Microsoft Teams - Oliver C. Logroño; Adelyne M. Costelo-Abrea (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper investigated how teachers and students of English as a Second Language view the effectiveness of Microsoft Teams for remote and online learning. This research employed descriptive survey and qualitative methods, which involved a questionnaire and an interview for data collection. Teachers and students of English as a Second Language were surveyed and interviewed about their perceptions of Microsoft Teams' usefulness. Frequencies and percentages were employed as statistical methods for the study. The results revealed that teachers and students have positive perceptions of Microsoft Teams. In an online class, Microsoft Teams optimally supports and favors the learning environments of students. In addition, the findings indicate that Microsoft Teams is an effective virtual learning platform due to its quality, user friendliness, and functionalities. Teacher participants perceived that the tool played an important role in promoting interactive learning and receiving and providing feedback.